Evaluation of Volatile Compounds during the Fermentation Process of Yogurts by Streptococcus thermophilus Based on Odor Activity Value and Heat Map Analysis - Li Zhang; Si Mi; Ruo-bing Liu; Ya-xin Sang; Xiang-hong Wang (International Journal of Analytical Chemistry)
The volatile composition of yogurt produced by Streptococcus thermophilus fermentation at different time points was investigated by gas chromatography-mass spectrometry combined with simultaneous distillation and extraction. A total of 53 volatile compounds including 11 aldehydes, 10 ketones, 8 acids, 7 benzene derivatives, 13 hydrocarbons, and 4 other compounds were identified in all of the samples. Ketones and hydrocarbons were the predominant volatile components in the early stage, whereas acids were the predominant volatiles in the late stage. The importance of each volatile was evaluated based on odor, threshold, and odor activity values (OAVs). Twenty-nine volatiles were found to be odor-active compounds (OAV > 1), among which (E, E)-2,4-decadienal had the highest OAV (14623–22278). Other aldehydes and ketones such as octanal, dodecanal, 2-nonen-4-one, and 2-undecanone also showed high odor intensity during fermentation. Heat map analysis was employed to evaluate the differences during fermentation. The results demonstrated that the volatile profile based on the content and OAVs of volatile compounds enables the good differentiation of yogurt during fermentation.